Experimental Study on the Evolution of Fracture Aperture of Single-Fracture Granite during Liquid Nitrogen Cold Shock Cycling - Haiping Niu; Weidong Yu (Geofluids)
Fractures in hot dry rock (HDR) reservoirs are the locations where heating fluid flows exchange heat with the HDR matrix. Cold shock with liquid nitrogen is one method for stimulating cracks. This study investigates the evolution law of fracture aperture under cold shock with liquid nitrogen. The real-time high-temperature triaxial servo control rock testing machine was used to conduct permeability experiments to examine the fracture aperture of single-fracture granite during liquid nitrogen shock cycles at various temperatures. The effects of pore pressure, temperature, and shocking cycles on the fracture aperture are analyzed, and the difference in fracture aperture variation under liquid nitrogen cooling and natural cooling modes is compared. The results showed that (1) during liquid nitrogen cooling, the fracture aperture expands as pore pressure rises; the effect of pore pressure on the fracture aperture becomes more robust as the number of liquid nitrogen shocking cycles and initial temperature increases; (2) under 1-2 soaking cycles, fracture aperture decreases as the temperature rises. Under two or more soaking cycles, the fracture aperture first increases and then decreases with increasing temperature; (3) when the initial temperature of fractured granite is 100°C, the fracture aperture is not significantly changed by repeated cold soaking cycles. However, with a higher initial temperature, the fracture aperture develops with more liquid nitrogen cold soaking cycles. The liquid nitrogen cooling method is more conducive to increasing the fracture aperture than natural cooling. The experimental results can provide primary experimental data for future research into controlling the evolution of granite cracks.